Depression, anxiety, stress and life satisfaction in patients with chronic spontaneous urticaria (Annals of Medical Research, 2022)
Aim: Chronic Spontaneous Urticaria (CSU) is the skin diseases with high rates of comorbid psychopathology. The aim of this study was to assess the relationship between CSU and anxiety, depression, stress and life satisfaction.Materials and Methods: 204 people were included in the study. 101 were CSU patients and 103 were healthy control participants. Demographic and clinical characteristics were obtained by the Questionnaire created by the research team. Depression Anxiety Stress Scale (DASS) and Satisfaction with Life Scale were used to assess psychological status and life satisfaction. Statistical analysis was performed using SPSS version 17.Results: Stress and anxiety scores (15,88±6,73 to 13,33±6,05, p
Keywords: Urticaria; Depression; Anxiety Stress; Life Satisfaction; Psychological intervention